Putting It All Together: Adding Value to the Global Ocean and Climate Observing Systems With Complete Self-Consistent Ocean State and Parameter Estimates - Heimbach, Patrick; Fukumori, Ichiro; Hill, Christopher N.; Ponte, Rui M.; Stammer, Detlef; Wunsch, Carl; Campin, Jean-Michel; Cornuelle, Bruce; Fenty, Ian; Forget, Gaël; Köhl, Armin; Mazloff, Matthew; et al. (Frontiers in Marine Science, 2019)
In 1999, the consortium for Estimating the Circulation and Climate of the Ocean (ECCO) set out to synthesize the hydrographic data collected by the World Ocean Circulation Experiment (WOCE) and satellite sea surface height measurements into a complete and coherent description of the ocean afforded by an ocean general circulation model. Twenty years later, the versatility of ECCO's estimation framework enables production of global and regional ocean and sea-ice state estimates that incorporate not only the initial suite of data and its successors, but nearly all data streams available today. New observations include measurements from Argo floats, marine mammal-based hydrography, satellite retrievals of ocean bottom pressure and sea surface salinity, and ice-tethered profiler data in polar regions. The framework also produces improved estimates of uncertain inputs, including initial conditions, surface atmospheric state variables, and mixing parameters. The freely available state estimates and related efforts are property-conserving, allowing closed budget calculations that are a requisite to detect, quantify, and understand the evolution of climate-relevant signals as mandated by the Coupled Model Intercomparison Project Phase 6 (CMIP6) protocol. The solutions can be reproduced by users through provision of the underlying modeling and assimilation machinery. Regional efforts have spun off that offer increased spatial resolution to better resolve relevant processes. Emerging foci of ECCO are on global sea level change, in particular contributions from polar ice sheets, and the increased use of biogeochemical and ecosystem data to constrain global cycles of carbon, nitrogen and oxygen. Challenges in the coming decade include provision of uncertainties, informing observing system design, globally increased resolution, and moving toward coupled Earth system estimation with consistent momentum, heat and freshwater fluxes between the ocean, atmosphere, cryosphere and land.